2004
DOI: 10.1007/s10761-004-1135-0
|View full text |Cite
|
Sign up to set email alerts
|

Wild Cattle: Red Deer in the Religious Texts, Iconography, and Archaeology of Early Medieval Ireland

Abstract: Humans use animals as a means of creating and manipulating relationships with other human beings. This process occurs both through the use of animals for food or raw materials and through the use of animals as literary and artistic symbols.Cervus elaphus is Ireland's only indigenous deer species. It is also unique in being the only native Irish, wild animal to appear frequently in medieval texts, iconography, and archaeological deposits. This paper brings together diverse sources of information to illuminate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These assemblages are similar to Lough Yoan north crannog with a dominance of cattle, followed by sheep and possibly pig, with small amounts of horse and red deer and again possibly goat 25 . The occurrence of horse DNA at Lough Yoan may also reflect its consumption (as at Sroove), whilst the occurrence of red deer is thought-provoking as this was a prestige food closely associated with cattle in the early medieval mind 26 . The bile acid data supports the presence of these domesticates as live animals along with faecal material from human sources.…”
Section: Discussionmentioning
confidence: 99%
“…These assemblages are similar to Lough Yoan north crannog with a dominance of cattle, followed by sheep and possibly pig, with small amounts of horse and red deer and again possibly goat 25 . The occurrence of horse DNA at Lough Yoan may also reflect its consumption (as at Sroove), whilst the occurrence of red deer is thought-provoking as this was a prestige food closely associated with cattle in the early medieval mind 26 . The bile acid data supports the presence of these domesticates as live animals along with faecal material from human sources.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Andone, the benefits of a biographical approach have already been reaped within individual specialist fields; for example, the study of animal remains at Launceston Castle (Albarella & Davis, 1996) has demonstrated how changes in the culling and consumption of animals can be linked to broader social changes, while the importance of deer and the social discourse associated with them has been the subject of multiple studies (e.g. Soderberg, 2004;Sykes, 2005Sykes, , 2007Thomas, 2007). Ceramics can also provide, amongst other things, insights into social status and site experience (Jervis, 2014: 103) and the way in which occupation practices altered through time, as at Sandal (Moorhouse, 1986).…”
Section: Towards a Biographical Methodologymentioning
confidence: 99%
“…And the zooarchaeology of later Europe, medieval, and more recent historical periods also is a topic of considerable study. Topics include specific case studies of religious orders and communities, exotic animal use, hunting, butchering, diet, and nutrition (Albarella and Thomas 2002;Ayres et al 2003;Baxter and Hamilton-Dyer 2003;Crader 2003;Hoffmann 2001;Lentacker and Ervynck 1999;Polet and Katzenberg 2003;Serjeantson 2001;Soderberg 2004;Thomas 2005Thomas , 2007Woolgar et al 2006).…”
Section: Political Economic Use Of Animals In Europementioning
confidence: 99%